Estimation of Interstock and Intermediate Stock Usefulness for Summer Pear Cvs. Budded on Two Rootstocks - Sosna Ireneusz; Kortylewska Daria (Journal of Horticultural Research, 2013)
In order to increase the profitability of pear production, a greater density of weak growing trees per area unit should be planted. In Poland, the most frequently used pear dwarfing rootstocks are quince clones. The main disadvantage of them is a physiological incompatibility with some cultivars. The aim of this study was to evaluate the effect of the rootstock, interstock, and intermediate stock on growth and productivity of two summer pear cultivars, which are not compatible with the quince rootstock. Twoyear- old pear trees of ‘Radana’ and ‘Clapp’s Favourite’ cvs of different compositions were planted in the spring 2006. The following combinations were evaluated: ‘Radana’ and ‘Clapp’s Favourite’ on Caucasian pear seedlings, ‘Radana’ and ‘Clapp’s Favourite’ on quince SI with an intermediate stem piece of ’Doyenne du Comice’ and ‘Radana’ on Caucasian pear with ‘Pyrodwarf’ interstock. Up to the 6th year after planting, trees of ‘Radana’ grafted on Caucasian pear seedlings and on quince with intermediate stock yielded better than ‘Radana’ trees composed of Caucasian pear seedling and ‘Pyrodwarf’ interstock. ‘Clapp’s Favourite’ in all combinations had significantly heavier fruits. The highest crop efficiency index had ‘Radana’ on quince with ’Doyenne du Comice’ intermediate stock.